Double‐Layer Structural Compatible Protective Material with Excellent Microwave Absorption and Heat Shielding Performance - Ziyu Wang; Huifang Pang; Hao Lei; Meng Wang; Yuping Duan (Advanced Materials Interfaces)
Abstract In view of the practical demands and mechanistic conflicts between microwave absorption and heat shielding compatibility, a double‐layer composite coating based on moth‐eyed hexagonal anti‐reflective structure is prepared by combining the advantages of metamaterials and coatings. The hexagonal periodic sequential configuration of the upper infrared shield layer (IRSL) can break the continuity of the electric field, induce a networked concentration of the surface current and internal electric field of the microwave absorption layer, thus optimizing the impedance matching and counteract the attenuated absorption performance due to the high dielectric IRSL. In addition, the emissivity of IRSL can be tuned artificially by changing the filler composition and particle size. The structural double‐layer composite coatings have a maximum effective absorption (reflection loss←10 dB) bandwidth of 7.4 GHz in the SKu bands at deep subwavelength thickness, while the infrared emissivity is 0.292. This work provides a novel approach for multispectral modulation in the field of advanced compatible protection systems.